2019
DOI: 10.1039/c9nr06866j
|View full text |Cite
|
Sign up to set email alerts
|

Co/Pd-Based synthetic antiferromagnetic thin films on Au/resist underlayers: towards biomedical applications

Abstract: Thin film stacks made of multiple repeats of Co/Pd-based SAF units with perpendicular magnetic anisotropy and tunable magnetic moment were explored as starting material to fabricate free-standing micro/nanodisks for theranostic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…19 More recently, the significant robustness of [Co/Pt(Pd)] N MLs along with the capability to grow on different rigid and flexible substrates while preserving their magnetic properties have further expanded the field of applications. They have been proposed, for example, as suitable materials for the preparation of freestanding micro-/nanodisks for biomedical applications 20 or as key components of flexible PMA-GMR spin valves 8 for a new generation of flexible magnetoreceptive devices with a great potential for application in human-machine interfaces. 7 Furthermore, it has been recently observed that the FM/ HM interface allows the stabilization of peculiar chiral spin configurations such as skyrmions 21−23 and homochiral Neéltype domain walls (DWs).…”
Section: Introductionmentioning
confidence: 99%
“…19 More recently, the significant robustness of [Co/Pt(Pd)] N MLs along with the capability to grow on different rigid and flexible substrates while preserving their magnetic properties have further expanded the field of applications. They have been proposed, for example, as suitable materials for the preparation of freestanding micro-/nanodisks for biomedical applications 20 or as key components of flexible PMA-GMR spin valves 8 for a new generation of flexible magnetoreceptive devices with a great potential for application in human-machine interfaces. 7 Furthermore, it has been recently observed that the FM/ HM interface allows the stabilization of peculiar chiral spin configurations such as skyrmions 21−23 and homochiral Neéltype domain walls (DWs).…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the individual layers and the number of repetitions in the [Co/Pd] stack were selected to ensure i) perpendicular magnetic anisotropy; ii) strong and compensated antiferromagnetic coupling in the SAF structure; and iii) two stable parallel/antiparallel magnetization configurations in the spin valve layer stack. [48] A capping layer of Pd (2.1 nm) was deposited to prevent the magnetic free layer from oxidation. All the layers were deposited under an Ar pressure of 3.5 × 10 −3 mbar while the deposition rate was set to 0.067 nm s −1 (24 W) for Au, 0.03 nm s −1 (40 W) for Ta, 0.04 nm s −1 (26 W) for Pd, 0.025 nm s −1 (52 W) for Co, and 0.03 nm s −1 (48 W) for Ru.…”
Section: Methodsmentioning
confidence: 99%
“…52,53 A Pd(2.1) capping layer was deposited on top to prevent the FL oxidation. The single layers' thickness and the number of repetitions of the [Co/Pd] N multilayers were selected on the basis of our previous work 54 with the aim to ensure (i) a PMA along the full layer stack, (ii) a strong and compensated antiferromagnetic coupling in the SAF structure, and (iii) two stable parallel/antiparallel magnetization congurations in the spin-valve system. A 10 nm thick weakly-adhering Au underlayer [46][47][48][49] was interposed between the SiO x /Si(100) substrate and the GMR-SV to favour the transfer of the heterostructure on a exible tape.…”
Section: Methodsmentioning
confidence: 99%